Optimasi Pemakaian Sendiri PLTU dengan Metode Audit Energi pada Motor Listrik 3 Fasa di PLTU X - Rio Afrianda; Samsurizal Samsurizal (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2020)
PLTU X is an industrial power plant with a large consumption of electrical energy for its own use. In ISO50001, every industry with a large Energy Consumption Intensity (IKE) needs to be audited for energy consumption. The company performance contract also regulates that the percentage of own use should not exceed 6% of electricity production. Currently, the percentage of own use in PLTU X unit 5 is greater than unit 4. For this reason, it is necessary to conduct an energy audit for own use with the aim of reducing the percentage of own use in unit 5 by 0.5% from current conditions and finding opportunities for energy savings at PLTU X unit 5. To analyze this problem using the energy audit method, analysis using the performance test method using the "gate cycle" and testing the quality of the voltage source by measuring using power quality analysis. After finding the equipment with the greatest energy consumption, fish bone tools were used to find the main cause of this abnormality.